1994
DOI: 10.1083/jcb.125.6.1251
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalized structure of the plasma membrane for receptor movements as revealed by a nanometer-level motion analysis.

Abstract: Abstract. Movements of transferrin and cz2-macroglobulin receptor molecules in the plasma membrane of cultured normal rat kidney (NRK) fibroblastic cells were investigated by video-enhanced contrast optical microscopy with 1.8 nm spatial precision and 33 ms temporal resolution by labeling the receptors with the ligand-coated nanometer-sized colloidal gold particles. For both receptor species, most of the movement trajectories are of the confined diffusion type, within domains of =0.25/zm 2 (500-700 nm in diago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
244
3
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(266 citation statements)
references
References 53 publications
17
244
3
2
Order By: Relevance
“…The filaments prevent free diffusion of proteins and complexes with bulky cytoplasmic protrusions. Although such proteins and complexes are free to diffuse within each partition of the grid, intercompartment movement is restricted (4,6,26,29,30). In the picket scenario, bulky cytoplasmic domains are not required for confinement.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The filaments prevent free diffusion of proteins and complexes with bulky cytoplasmic protrusions. Although such proteins and complexes are free to diffuse within each partition of the grid, intercompartment movement is restricted (4,6,26,29,30). In the picket scenario, bulky cytoplasmic domains are not required for confinement.…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of SPT and fluorescence recovery after photobleaching studies, several groups have concluded that the plasma membrane is partitioned by actin filaments on the cytosolic surface into nanocompartments that allow rapid local diffusion of proteins and lipids within them but suppress long-range diffusion that involves intercompartment movement (4,6,26). To explain the effects of cortical actin, a membrane skeleton ''fence'' or ''corral'' model and an anchored-transmembrane protein ''picket'' model (4,5,27,28) have been proposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar domain sizes have been found for NK2R in HEK293 cells (35): Fluorescence recovery after photobleaching experiments revealed domains of radius ϭ 420 Ϯ 80 nm without ligand and 170 Ϯ 50 nm when agonist was bound. The larger domains could arise from confinement by a membrane-skeleton͞cytoskeleton fence structure (32,36) or from long-range protein interactions (31) and might represent a population average of the two larger compartments found here. Because OR17-40 is constitutively internalizing, the smaller domains are likely to correspond to precursors of clathrincoated pits (35,37).…”
Section: Discussionmentioning
confidence: 99%
“…For the two dimensional reactions in the cell membrane, G-protein activation and receptor phosphorylation, we used values of D = 10 −11 -10 −9 cm 2 /sec (Lee et al, 1993;Sako and Kusumi), SA = 1000 μm 2 , and [G] = 10 -100/μm 2 (Pardo et al, 1997). For G-protein activation we then calculate range for k + of 10 −6 to 10 −3 (#/cell) −1 sec −1 .…”
Section: Estimating the Role Of Diffusionmentioning
confidence: 99%